Peran Strategis E-resource Perpustakaan Perguruan Tinggi dalam Menunjang Akreditasi Program Studi - Rhoni Rodin (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This paper discusses the role of e-resource strategic libraries of universities in supporting the accreditation of study programs. The existence of a library is very influential for the success of the learning process in various levels of education ranging from elementary school to college. A library is a heart of a college. Therefore, the library must provide quality information resources in accordance with the expectations of academic community. One of some resources that has a strategic role in supporting the accreditation of study program is an e-resource. There are various types of e-resources that can be developed by the library of e-journals, e-books, full script databases, index databases, and so forth. All of them have a very strategic position in supporting accreditation of study programs. There is a standard library that will be assessed by the assessor team.